Kryl'ia . Wings - Shepitko, Larisa (Mosfilm, 1966)
Duration: 01:30:00 This film is about the fortunes of former war heroine flyer, Nadezhda Petrukhina, who is working as a schoolteacher in the aftermath of the war and becoming increasingly dissatisfied with her lot. Her daughter Tanya has married an older man, Igor, who Petrukhina clearly thinks isn't good enough for her, while the teacher is herself courted by a museum director, Pavel Gavrilovich. Centring on the former lady flyer and taking the film at a nice slow pace, we follow her through several days and activities such as going to a museum, catching up with old friends at the airfield, or meeting Igor's more intellectualised friends. Her attempts to compensate for her distraction lie in tendencies of appearing authoritative. But the students and her daughter distrust and despise her because of her innability to be herself. In distress, she is forced even more deeply into reliving her memories of the only time in which she was truly alive, seeking some kind of answer or resolution.